Leaving the Bakunin barracks for the front. Garcia Oliver in the middle; Sanz at the right. Series of 5 photos. Copied from CNT collection
Leaving the Bakunin barracks for the front. Garcia Oliver in the middle; Sanz at the right. Series of 5 photos. Copied from CNT collection.